PENGARUH HERDING DAN OVERCONFIDENCE TERHADAP KEPUTUSAN INVESTASI: Studi Pada Nasabah Emas Kantor Pegadaian Ungaran - Ria Restu Daniati; Hendra Dwi Prasetyo (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
An investment decision is a program or a procedure to allocate an asset into an investment activity, where the investment activity can provide income in the form of profit by having a non-pendding age for the future, therefore the investment decision must be decided carefully, because it has a high risk. The behavior of investors to consider an investment decision often overcomes many cyclological impulses such as social factors and cognitive factors that have investor treatment change iraisonal. This research has been carried out to analyze the harassing and overdonfidence of the decisions of gold investais with the object of researching the sub-branch of unharan. There are ninety-six people who have gold savings from the Unharan Sub-Branch Pawnshop. Sampling researchers using accidental sample techniques. The data analysis techniques used by this study are validity test, reliability test, classical assumption test and hypothesis test